+0  
 
-1
451
1
avatar+1015 

Simplify.

27x6y3−−−−−−√3

Assume all variables are nonnegative.

AngelRay  Dec 20, 2017

Best Answer 

 #1
avatar+20008 
+2

Simplify.

cuberoot(27x^6y^3)

Assume all variables are nonnegative.

 

\(\begin{array}{|rcll|} \hline && \sqrt[3]{27x^6y^3} \\ &=& \sqrt[3]{3^3x^3x^3y^3} \\ &=& \sqrt[3]{3^3}\sqrt[3]{x^3}\sqrt[3]{x^3}\sqrt[3]{y^3} \\ &=& 3xxy \\ &=& 3x^2y \\ \hline \end{array}\)

 

laugh

heureka  Dec 20, 2017
 #1
avatar+20008 
+2
Best Answer

Simplify.

cuberoot(27x^6y^3)

Assume all variables are nonnegative.

 

\(\begin{array}{|rcll|} \hline && \sqrt[3]{27x^6y^3} \\ &=& \sqrt[3]{3^3x^3x^3y^3} \\ &=& \sqrt[3]{3^3}\sqrt[3]{x^3}\sqrt[3]{x^3}\sqrt[3]{y^3} \\ &=& 3xxy \\ &=& 3x^2y \\ \hline \end{array}\)

 

laugh

heureka  Dec 20, 2017

22 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.